2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090521
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of low cost game-based balance rehabilitation tool using the microsoft kinect sensor

Abstract: The use of the commercial video games as rehabilitation tools, such as the Nintendo WiiFit, has recently gained much interest in the physical therapy arena. Motion tracking controllers such as the Nintendo Wiimote are not sensitive enough to accurately measure performance in all components of balance. Additionally, users can figure out how to "cheat" inaccurate trackers by performing minimal movement (e.g. wrist twisting a Wiimote instead of a full arm swing). Physical rehabilitation requires accurate and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
155
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(176 citation statements)
references
References 12 publications
1
155
0
8
Order By: Relevance
“…Also based on motion tracking, the work by Lange et al [12] proposes a gamification approach to physical rehabilitation, in which a low cost depth sensing camera is used together with a game of balance training for adults suffering from neurological injury. Given that cameras can impose constraints regarding the patient's relative position to the camera, Daponte, de Vito, and Sementa [13] proposed a system based on wearable Inertial Measurements Units (IMUs) for range of limb motion measurement in home rehabilitation.…”
Section: Audiovisual Biofeedbackmentioning
confidence: 99%
“…Also based on motion tracking, the work by Lange et al [12] proposes a gamification approach to physical rehabilitation, in which a low cost depth sensing camera is used together with a game of balance training for adults suffering from neurological injury. Given that cameras can impose constraints regarding the patient's relative position to the camera, Daponte, de Vito, and Sementa [13] proposed a system based on wearable Inertial Measurements Units (IMUs) for range of limb motion measurement in home rehabilitation.…”
Section: Audiovisual Biofeedbackmentioning
confidence: 99%
“…Moreover, there are also some applications in developing health-care, rehabilitation or in-home activity monitoring of elders. For example, Lange, et al [15] developed a low-cost balance rehabilitation tool using Kinect and Stone and Skubic [16] also presented a Kinect-based system to monitor elderly adults to avoid fall risk while performing in-home activity.…”
Section: System Overviewmentioning
confidence: 99%
“…With the emergence of Kinect for Windows, because of Kinect's diversified functions and low price (Zhang, 2012) Nowadays, the use of the commercial video games as rehabilitation tools has gained much interest in the physical therapy arena (Lange et al 2011). Kinect as a new type of console has lots of advantages in rehabilitation training for children with mental retardation, which are proved to be more effective than those traditional methods (Yeung et al 2014).…”
Section: Kinect a Supportive Sensor For Rehabilitationmentioning
confidence: 99%
“…The first advantage of Game System for Rehabilitation based on Kinect is the low cost, which allows more people to get the rehabilitation medical training (Lange et al 2011). As Laura (2013) pointed out, the low cost video games based on motion capture are potential tools in the rehabilitation context in exceptional child, whose research had showed improvements in balance and ADL in CP participants in a school environment (Luna-Oliva et al 2013).…”
Section: Kinect a Supportive Sensor For Rehabilitationmentioning
confidence: 99%